Literatur Review : Pengaruh Tradisi Mengunyah Sirih Terhadap Kesehatan Gigi - Aditya, Ronal Surya; Alifatunnisa, Alifatunnisa; Elvarelta, Chysaura Malva; Adhitama, Felicia Dewati Elit; Khusna, Nasya Zilza; Betay, Oskar; Andayani, Sari Dewi (Prosiding Seminar Kesehatan Nasional Sexophone, 2024)
The habit of nginang (chewing betel), which has been practiced for generations in various tribes in Indonesia, has various health benefits. The belief that chewing betel nut can prevent oral diseases and treat toothache and bad breath may be deeply ingrained among its users. The purpose of this study was to explore an in-depth understanding of the phenomena relevant to this research topic. This study used the literature review.method by taking ten different article titles with the criteria of selecting literature sources covering the time span of publication in the last ten years in order to include current and relevant information. Literature sources were obtained through searching using the search engine "Google Scholar" with relevant keywords. This study was conducted with the aim of gaining a deeper understanding of the phenomenon. The results showed that one of the main benefits of betel chewing is improved oral health. In addition, there are potential dangers that can cause damage to the teeth and periodontal tissues, especially when done excessively or with certain chemicals. Therefore, efforts to strengthen and preserve the betel chewing habit can also be seen as a step to preserve the culture and identity of a community.This study provides valuable insights into the relationship between the traditional practice of nginang (chewing betel) and dental health, as well as cultural preservation efforts in Indonesian society.